(untitled) (Международный научный журнал «Инженер», 2026)
All over the world the demand for railway transport of goods and passengers is increasing, which is the reason for increasing the requirements for all railway facilities. Every sphere of railway facilities is developing, new techniques and technologies are being introduced, but despite such changes and developments, the railway has not yet escaped from technical difficulties and defects that lead to faulty conditions. The occurrence of track defects and defects in the junction zone on the sections with high-speed and heavy-weight train traffic, deterioration of track geometry, destruction of track rigidity, occurrence of faults under the influence of various factors are also important with the increase of vibrodynamic actions and vibrations. So, the abovementioned aspects are put forward as the main problems to be reduced, the causes of these deficiencies, faults and effects and the measures to eliminate and reduce them are given in this article.